PENGARUH ETIKA KERJA ISLAMI DAN KEPUASAN KERJA KARYAWAN TERHADAP KOMITMEN PADA ORGANISASI - Lestari, Sri; -, Karlina (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2020)
is intended to analyze the influence of Islamic work ethic and job satisfaction on commitment to the organization in PT. Berkah Agung Sejati Bekasi. Research Population in this research is all permanent employees in officer section at PT Berkah Agung Sejati. Sampling using non probability sampling with the number of samples of 33 respondents.Data analysis method used is descriptive analysis method and quantitative research, with multiple linear regression analysis technique. The results partially show the work ethic of Islami and positive to commitment at organization and job satisfaction significant and significant to commitment at organization. The result of simultaneous testing with f test shows Islamic work ethic and cooperation satisfaction equals with commitment to organization. Islamic work ethic and employee job satisfaction give influence equal to 68,7% while rest of 31,3% donated by other factor not in this research.